A Case Role of Verbs in the Movie Script Harry Potter and the Chamber of Secret - Dewi Astari Putri, Ni Nyoman (Humanis, 2018)
This writing entitled “A Case Role of Verbs in the Movie Script Harry Potter and the Chamber of Secret” was conducted in order to be able to identify the types of verb, to find out the semantic structure and the case role between the verb and its cases.The data in this study were taken directly from clauses and sentences found in the movie script. Those data were collected using the documentation method and note taking technique. In analyzing the data, Case Grammar theory proposed by Walter Cook (1979) was applied by qualitative method. In addition, in order to present the data analysis clearly and neatly, informal method was used to describe and explain the data.The result shows that there were three types of verbs found in the movie script. Those verbs are state, process, and action verbs. In addition, the semantic structure of the data is shown by using case frames. The case frames of the data are basic state, basic process, basic action, state experiential, process experiential, action experiential, state benefactive, process benefactive, action benefactive, state locative, process locative, and action locative verb. Besides, the case role of the datain surface structure is as agent, experiencer, benefactive, object, and locative. Furthermore, the analysis of deep structure showed that there are three covert case roles found in the data namely lexicalized, coreferential, and build-in.